(untitled) (Bangladesh Veterinarian, 2012)
Influenza A virus, subtype H5N1 causes a fatal disease in domestic poultry and could spread directly from poultry to humans. The aim of this study was to develop a multiplex reverse transcription polymerase chain reaction (mRT-PCR) for simultaneous detection of Type A influenza virus-specific matrix protein (M) gene as well as H5 and N1 genes of highly pathogenic avian influenza (HPAI) viruses. Finnzymes Phusion-Flash High- Fidelity PCR Master Mix (Finnzymes Oy, Finland) and Qiagen one-step RT-PCR enzyme mix (Qiagen, Germany) were used in a one-step RT-PCR. RNA was extracted from two known positive samples using Qiagen RNA extraction kit. RT-PCR was carried out with a mixture of primers specific for the Type A influenza virus matrix protein (M), and H5 and N1 genes of H5N1 HPAI viruses in a single reaction system. The mRT-PCR cDNA products were visualized by gel electrophoresis. The mRT-PCR yielded fragments of 245 bp for M, 545 bp for H5 and 343 bp for N1 genes of HPAI virus, which were clearly distinguishable. The mRT-PCR using the Finnzymes Phusion-Flash High-Fidelity PCR Master Mix (Finnzymes Oy, Finland) with Qiagen one-step RT-PCR Enzyme Mix (Qiagen, Germany) required only one hour and 20 minutes. (Bangl. vet. 2011. Vol. 28, No. 2, 55 59) DOI: http://dx.doi.org/10.3329/bvet.v28i2.10653